PENERAPAN MEDIA CANVA DALAM MENINGKATAN HASIL BELAJAR SISWA PADA MATERI KEUNIKKAN DAERAH TEMPAT TINGGALKU DI KELAS IV SD AL WASHLIYAH 01 MEDAN - Haliza Luthfia; Nurjannah (Global Action and Education for Society, 2026)
Engaging and interactive learning media are essential to enhance students’ participation and understanding in the learning process. This study aims to improve students’ learning outcomes through the implementation of Canva media in classroom instruction. The subjects of this study were 15 fourth-grade elementary school students. The method used was Classroom Action Research (CAR), conducted in two cycles. The instruments included observation sheets and learning outcome tests. The results showed an improvement in students’ learning outcomes from Cycle I to Cycle II. In Cycle I, the percentage of students achieving mastery was 60%, which increased to 86.67% in Cycle II. This improvement indicates that the use of Canva media helps teachers deliver material in a visual, engaging, and interactive way, thereby enhancing students’ understanding. Thus, Canva media is effective as an instructional aid to improve students’ learning outcomes.